Zarządzanie ryzykiem w przedsięwzięciach inwestycyjnych jednostek samorządu terytorialnego - Dylewski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article covers the concept of risk expressed as the probability of events with negative financial effects. In aspect of more complicated and capital-intensive undertakings and programmes in local government there were risen problems of risk management. Stages of investment process determine prediction and estimation of risk probabilities. How to minimise risk and possible loses it's the main question in the article, especially in the new conditions of self-government activity.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 282-291